PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. REKSA FINANCE JAKARTA SELATAN - Tommy Gala Pratama; 2Irma Sari Octaviani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the effects of leadership style and work ethic on employee performance at PT Nusalima Digdaya Nusantara. The research employed a quantitative approach, with data collected through questionnaires distributed to 56 respondents. Data analysis was conducted using simple and multiple linear regression to test the research hypotheses. The results show that leadership style (X1) has a positive and significant effect on employee performance (Y), as indicated by a t-value of  3.580 > t-table 1.290 and a significance level of 0.000 > 0.05. Meanwhile, work ethic (X2) has a positive and significant effect on employee performance, with a t-value of 11.482 > t-table 1.290 and a significance level of 0.000 < 0.05. Simultaneously, leadership style and work ethic have a positive and significant effect on employee performance, as indicated by an F-value of 64.706 > F-table 3.09 and a significance level of 0.000 < 0.05. In conclusion, employee performance at PT Nusalima Digdaya Nusantara can be improved by strengthening work ethic while continuously developing effective leadership practices.